Combination of photodynamic therapy and phototherapy for the treatment of cutaneous open wounds in dogs-case reports - Sampaio, Alexandre B. A.; Rahal, Sheila C.; Branco, Marina P.; Abibe, Rebeca B.; Dorth, Henrique O.; Coris, Jeniffer G. F.; Almeida-Lopes, Luciana (Univ Zagreb Vet Faculty, 2021)
The evolution of cutaneous open wounds was evaluated in five client-owned dogs treated with photodynamic therapy (PDT), mediated by methylene blue and phototherapy with light-emitting diodes (LED) as the light source. On the first day of treatment, the wound was irrigated with sterile 0.9% sodium chloride solution, the surface was dried, and 3% solution of hydrogen peroxide soaked for 1 minute. The hydrogen peroxide was mechanically removed and, immediately after, 0.01% methylene blue was used in the wound for five minutes, after which a cluster of red LEDs (650 -670 nm wavelength, 350 mW power, and irradiance of 200 mW/cm2) was used. Subsequently, single phototherapy sessions, every 48 hours or more, were applied until wound healing. In general, 24J was used for PDT and 12J for phototherapy. In all cases, the cutaneous open wounds treated with PDT associated with phototherapy healed without complications, and it may be considered as a treatment option, especially for extensive lesions.
Keywords: healing; photodynamic therapy; light-emitting diode; wound